2013
DOI: 10.1016/j.jcf.2013.03.006
|View full text |Cite
|
Sign up to set email alerts
|

The effect of gastric juice on interleukin-8 production by cystic fibrosis primary bronchial epithelial cells

Abstract: Patients with CF, treated with PPIs, have GJ with high pH and high endotoxin levels. These patients often have GER and bronchial aspiration. The aspirated material (GJ "on" PPI) has a significantly enhanced inflammatory effect on CF bronchial epithelial cells in culture. As chronic PPI treatment in CF may result in a paradoxically increased inflammatory effect in the airways, alternative anti-reflux therapies should be considered in CF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 28 publications
0
17
0
Order By: Relevance
“…It is notable that we found that expression of eight of the EoE genes failed to normalize to that found in the NL individuals; perhaps these refractory genes may explain the clinically observed relapsing propensity of PPI-REE 17 . Given the ability of PPI to modulate multiple components of the inflammatory axis, such as chemokines 6, 18, 19 , interleukins 20 , and vascular cell adhesion molecules 21 and mucosal barrier function 22 , the effects of high-dose, twice daily PPI may have an anti-inflammatory effect in addition to its effect on acid reduction 19 . Our study supports this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…It is notable that we found that expression of eight of the EoE genes failed to normalize to that found in the NL individuals; perhaps these refractory genes may explain the clinically observed relapsing propensity of PPI-REE 17 . Given the ability of PPI to modulate multiple components of the inflammatory axis, such as chemokines 6, 18, 19 , interleukins 20 , and vascular cell adhesion molecules 21 and mucosal barrier function 22 , the effects of high-dose, twice daily PPI may have an anti-inflammatory effect in addition to its effect on acid reduction 19 . Our study supports this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…Later, in a prospective study of CF patients randomized to placebo or esomeprazole, DiMango et al showed a trend towards earlier and more frequent exacerbations in patients randomized to PPI therapy [ 22 ]. Work by Pauwels et al offers a biological explanation to the above clinical findings; they demonstrated that gastric juice under the effects of PPI had a significantly enhanced inflammatory effect on CF bronchial epithelial cells as compared to gastric juice not affected by PPI [ 26 ]. This leads the authors to believe that PPI therapy in CF patients may result in paradoxically increased inflammatory effects on the airway.…”
Section: Discussionmentioning
confidence: 99%
“…However, it has been shown that the gastric juices of patients treated with PPI can induce interleukin‐8 production by bronchial epithelial cells in culture, and such effect is even more pronounced in cystic fibrosis patients known to have high inflammatory susceptibility. Accordingly, it has been suggested that chronic PPI treatment in cystic fibrosis might result in a paradoxically increased inflammatory effect on the airways . It is, therefore, tempting to speculate that PPI inhibitors could negatively affect airway inflammation in asthma patients through an unknown mechanism, resulting in worse disease control.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, it has been suggested that chronic PPI treatment in cystic fibrosis might result in a paradoxically increased inflammatory effect on the airways. 27 It is, therefore, tempting to speculate that PPI inhibitors could negatively affect airway inflammation in asthma patients through an unknown mechanism, resulting in worse disease control.…”
Section: Discussionmentioning
confidence: 99%